Contribuição ao estudo da aplicação da gestão econômica no processo de revisão tarifária das concessionárias de distribuição de energia elétrica no Brasil - Moge, José Eduardo (2010)
The electricity s ambient sector in it s various aspects has been modified and becoming more demanding, specially concerning to the fare price practised for electrical trade organizations and its consumers. Aneel, the regulatory agency, responsible for the fare review, uses for the obrainment of ingormations, basically, the accounting data of the organizations, which is elaborated through conventional concepts whose are not based on facts. The fair definition of the fare for the consumer, as well as the electrical trade distributor becomes necessary that informations used in the review process correspond to reality. Aneel is the responsibible for the settlement of the fares wich ensure to the consumer the right and fair electricity s payment, as well as assure the economic and financial equilibrium of the organization, to make possible the offer of a quality, trusty and continuous service. This practice is known in the concession contracts as modest fare . Is is realistc for the consumers and ecanomically satisfactory for the electrical trade organization, providing economic and financial balance. This way, this work emphasizes that Economic Management is the only management model which can measure the real economic value of organizations, that could be the group of concepts of Economic Management for being applied in the adjustment methodology and fare review of the electrical trade organizations, so this organizations can reach the economic and financial balance which is purposed in the concession. Therefore, the adjustment and fare review methodology was presented, created and used for Aneel during the price formation of the electricity and presenting a group of concepts that must support the organization. It can be concluded that financial and economical equilibrium purposed for the prices methodology of Aneel must be in step of facts and suppoted for a group of concepts considering the economical management and the application of the main components of this methodology brings conceptual impacts which must be later measured, through mathematical formulas which are components of the created methodology